Analisis Kesesuaian Konseptual terkait Penetapan Perjanjian Pengikatan Jual Beli sebagai Saat Terutangnya Pajak - Gymnastiar, Mochammad Giffari Al Hafidz; Taruna, Nugraha Wira; Yehezkia, Yehezkia; Merfol, Klivten Pieter (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The preparation of tax regulations, including regional taxes such as Land and Building Rights Acquisition Fee (BPHTB), must consider conceptual suitability. BPHTB is a tax on the transfer of ownership rights to land and/or buildings. However, there is a conceptual error in determining when BPHTB is due in Law Number 1 of 2022 concerning Central and Regional Financial Relations (HKPD Law). This determination is inconsistent with the concept of tax on transfer of ownership. In addition, there are differences between the provisions in the HKPD Law and its implementing regulations, which exacerbates conceptual problems. This research uses qualitative methods with literature studies to analyze these errors, including potential legislative errors related to the regulations when BPHTB is owed. The research results show that determining the signing of the Sale and Purchase Agreement (PPJB) as the time when the BPHTB is due is a conceptual error. In addition, there is a risk of inconsistent application of the law due to legislative errors, especially in cases of land and/or building sale and purchase transactions that are canceled and returned to the seller due to default. This error creates legal uncertainty and needs to be corrected to comply with applicable taxation concepts.